Bioelectrochemical enhancement of anaerobic digestion: Comparing single- and two-chamber reactor configurations at thermophilic conditions. (December 2017) - Liu, Si Ying; Charles, Wipa; Ho, Goen; Cord-Ruwisch, Ralf; Cheng, Ka Yu
Highlights: First study to assess the role of bioelectrodes on AD under thermophilic condition. Membraneless single- vs. cation exchange membrane two-chamber BES-AD were compared. The proclaimed positive role of bioelectrodes was found to be only short-lived. Biogas production in both BES-AD systems were suppressed due to VFAs build-up. BES may be more suitable to be an ex-situ unit for improving AD biogas quality. Abstract: Bioelectrochemical system (BES) can act as an auxiliary technology for improving organic waste treatment and biogas production in anaerobic digestion (AD). For the first time this study directly compared the performance of a single- and a cation-exchange membrane-equipped two-chamber BES-AD systems at thermophilic conditions. The results indicated that an active glucose-fed thermophilic anaerobic sludge could readily (<3 days) increase biogas production in both reactor configurations by inserting a carbon electrode poised at −0.8 V (vs. Ag/AgCl). However, after a 3-week operation, the biogas production rates from the single- and two-chamber BES reactor decreased due to volatile fatty acids accumulation. Only the two-chamber configuration could enable methane enrichment (98% CH4  v/v) in biogas. Overall, this study suggests that integrating bioelectrodes in-situ could not sustainably improve biogas production in a thermophilic AD reactor, and future studies should be directed towards the use of bioelectrodes for improving biogas quality.